13C-sucrose breath test for the non-invasive assessment of environmental enteropathy in Zambian adults - Schillinger, Robert J.; Mwakamui, Simutanyi; Mulenga, Chola; Tembo, Mizinga; Hodges, Phoebe; Besa, Ellen; Chandwe, Kanta; Owino, Victor O.; Edwards, Christine A.; Kelly, Paul; Morrison, Douglas J. (Frontiers in Medicine, 2022)
Objectives: Environmental enteropathy (EE) is a subclinical disorder highly prevalent in tropical and disadvantaged populations and is thought to play a role in growth faltering in children, poor responses to oral vaccines, and micronutrient deficiencies. This study aims to evaluate the potential of a non-invasive breath test based on stable isotopes for evaluation of impaired digestion and absorption of sucrose in EE. Methods: We optimised a 13C-sucrose breath test (13C-SBT) in 19 young adults in Glasgow, UK. In a further experiment (in 18 adults) we validated the 13C-SBT using Reducose®, an intestinal glucosidase inhibitor. We then compared the 13C-SBT to intestinal mucosal morphometry, immunostaining for sucrose-isomaltase (SI) expression, and SI activity in 24 Zambian adults with EE. Results: Fully labelled sucrose (0.3mg/kg) provided clear breath enrichment signals over 2-3 hours in both British and Zambian adults, more than five-fold higher than naturally enriched sucrose. Reducose® dramatically impaired 13C-sucrose digestion, reducing 4hr 13CO2 breath recovery by >50%. Duodenal biopsies in Zambian adults confirmed the presence of EE, and SI immunostaining was present in 16/24 adults. The kinetics of 13CO2 evolution were consistently faster in participants with detectable SI immunostaining. Although sucrase activity was strongly correlated with villus height (r=0.72; P<0.05) after adjustment for age, sex and body mass index, there were no correlations between 13C-SBT and villus height or measured sucrase activity in pinch biopsies. Conclusions: A 13C-SBT was developed which was easy to perform, generated clear enrichment of 13CO2 in breath samples, and clearly reports sucrase activity. Further work is needed to validate it and understand its applications in evaluating EE.